Start up India: Challenges & Opportunities (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2017)
Due to globalization and advancement in technology competition is increasing day by day thats why self- employment consciousness among college students is increasing at fast pace. Furthermore India is second most populous country and due to large population pressure it is need of hour to develop entrepreneurial skill among people in India so government launch startup India Plan to support young inspiring entrepreneur .This Paper aims to investigate the challenges and Opportunities in the way of startups in India. This paper is intent to explore the major difficulties faced by startups in India, and discuss the various opportunities of startups in India by using a literature-based analysis.